J. OCKMAN (ed) - Architecture School. Three Centuries of Educating Architects in North America - Valdivieso, Alejandro (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2016)
JOAN OCKMAN (ed) with REBECCA WILLIAMSON (research editor) Architecture School. Three Centuries of Educating Architects in North America MIT Press, Cambridge, Massachusetts -London, England, 2012 / Association of Collegiate Schools of Architecture, Washington D.C., 400 págs. 54,95 . Idioma: inglés (tapa dura)